2024
DOI: 10.3389/feart.2023.1340020
|View full text |Cite
|
Sign up to set email alerts
|

Can normalized difference vegetation index and climate data be used to estimate soil carbon, nitrogen, and phosphorus and their ratios in the Xizang grasslands?

Shaohua Wang,
Huxiao Qi,
Tianyu Li
et al.

Abstract: Accurately quantifying the relative effects of climate change and human activities on soil carbon, nitrogen, and phosphorus in alpine grasslands and their feedback is an important aspect of global change, and high-precision models are the key to solving this scientific problem with high quality. Therefore, nine models, the random forest model (RFM), generalized boosted regression model (GBRM), multiple linear regression model (MLRM), support vector machine model (SVMM), recursive regression tree model (RRTM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Previous studies have suggested that there are some uncertainties when using climate variables and NDVI to model plant and soil variables in terrestrial ecosystems. It included the accuracy of NDVI itself (such as easy saturation), the accuracy of climate variables (such as the error caused by spatial interpolation), the spatial-temporal matching error between dependent variables and independent variables, the acquisition time of dependent variables and topographic factors (such as slope) [25,26]. In this study, the random forest models of soil NH 4 + -N, NO 3 − -N and AP at only 0-10 cm and 10-20 cm were constructed, and soil depth can alter the model accuracies of these soil variables.…”
Section: Uncertainty Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have suggested that there are some uncertainties when using climate variables and NDVI to model plant and soil variables in terrestrial ecosystems. It included the accuracy of NDVI itself (such as easy saturation), the accuracy of climate variables (such as the error caused by spatial interpolation), the spatial-temporal matching error between dependent variables and independent variables, the acquisition time of dependent variables and topographic factors (such as slope) [25,26]. In this study, the random forest models of soil NH 4 + -N, NO 3 − -N and AP at only 0-10 cm and 10-20 cm were constructed, and soil depth can alter the model accuracies of these soil variables.…”
Section: Uncertainty Analysesmentioning
confidence: 99%
“…However, the extent to which the climate trivariate (temperature, precipitation and radiation) and NDVI can col-lectively explain variations in soil available nitrogen and phosphorus in alpine grasslands of the Qinghai-Xizang Plateau, compared to the climate trivariate alone, remains unknown due to a lack of relevant studies. Third, while previous research confirms that random forest algorithm is more accurate than other algorithms in quantifying pasture nutrient quality and nutrient pool, plant diversity, soil moisture, soil pH, soil carbon, nitrogen and phosphorus in alpine grasslands of the Qinghai-Xizang Plateau [22][23][24][25][26], it is uncertain whether the random forest algorithm also exhibits superior performance compared to other models in quantifying variations in soil-available nitrogen and phosphorus in alpine grasslands of the Qinghai-Xizang Plateau.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations